Screening for High Risk People with Diabetes Ulcer in the City of Pontianak - Titan Ligita; Sukarni Sukarni; Nada Westy Nurahayu; Safitri Solehah; Dialika Putri Miptaza; Riszki Safitri (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Diabetes mellitus is a health problem that can cause disorders or abnormalities in the feet, namely disorders of the nerves (neuropathy) and blood vessels (PAD). Peripheral arterial disease is a circulation problem where there is a narrowing of the arteries which results in reduced blood flow to the legs. Severe PAD is a major factor in lower extremity amputation, especially in patients with DM, then PAD in patients with DM can be seen with ischemic or gangrene injuries. Patients with DM have decreased blood circulation, especially in the lower extremities due to changes in the function of the endothelial layer due to a long hyperglycemic status. The change is a decrease in nitric oxide (NO) production. Another problem is the decrease in sensation in the feet because DM patients have a risk for neuropathy. This neuropathy causes DM patients to get injured easily because the area on the feet is not felt when traumatized, making it easier for infection to occur. Preventive action taken from the start is one of the best actions. Preventive measures in DM patients who experience circulation disorders and neuropathic problems can be done in several ways, including using tools and gymnastics. The tool used is Veinoplus arterial or electrical muscle stimulation, then the exercise in question is foot exercise. The working principle of this tool can increase blood circulation in the lower extremities by increasing the production of nitric oxide (NO), NO is an important component in preventing atherosclerosis which is one of the causes of blockage in blood vessels and can lead to injury and amputation. Therefore, improvement of circulation through certain interventions is needed to prevent these complications. Electrical muscle stimulation has been researched and proven to be able to increase circulation and improve sensation in people with DM. Therefore, this activity is expected to be able to contribute in preventing complications that can occur in people with DM. The objectives of this activity include identifying risk factors for circulation disorders and neuropathy in patients with DM, increasing public understanding of complications that can occur in DM patients, increasing the community's ability to prevent complications that can occur. While the output that can be generated from this activity is an increase in the knowledge of DM patients on the prevention of wound complications.